Consumer Behavior Of E-Commerce Users Of Udayana University Students - Yolivia Della Desia Purba; Ida Ayu Nyoman Saskara; Surya Dewi Rustariyuni (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
Consumptive behavior is the behavior of buying goods that are less necessary to fulfill personal satisfaction so that someone no longer distinguishes between needs and wants. The offers presented by e-commerce can be a risk for Udayana University students because they see it as an opportunity to tend to buy goods that may not be essential. When viewed physically, women tend to have more needs than men. So consumptive behavior must be accompanied by an understanding of the knowledge of managing money well. Financial literacy is very useful for students to avoid consumptive behavior. This study aims to see the effect of the use of e-commerce and financial literacy on the consumptive behavior of Udayana University students. The number of samples used in this study was 400 samples. The analysis techniques used were descriptive analysis techniques and Partial Least Squares (PLS) analysis. The results of this study indicate that the use of e-commerce has a positive and significant effect on the consumptive behavior of Udayana University students. This means that there is a unidirectional relationship between the variable of e-commerce use and the variable of consumptive behavior. Meanwhile, financial literacy has a negative effect on the consumptive behavior of Udayana University students. This means that there is a non-unidirectional relationship between the literacy variable and the consumer behavior variable.